2019
DOI: 10.2147/dmso.s227090
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diet, Diabetes Status, and Personal Experiences of Individuals with Type 2 diabetes Who Self-Selected and Followed a Low Carbohydrate High Fat diet</p>

Abstract: Background: Low carbohydrate high fat (LCHF) diets are increasing in popularity amongst patients with type 2 diabetes (T2D), however it is unclear what constitutes a sustainable LCHF diet in a real-world setting. Methods: This descriptive multi-method study characterized the diets, T2D status, and personal experiences of individuals with T2D who claimed to have followed an LCHF diet for at least 6 months. Participants completed a medications history, mixed-method dietary assessment, provided a blood sample, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
(44 reference statements)
1
27
0
4
Order By: Relevance
“…There is a general perception that the foods included in an LCHF diet are expensive and that most of the people who decide to follow this lifestyle in South Africa are reasonably affluent [22]. This is consistent with the perception that LCHF diets are too expensive for people living in under-resourced communities [23].…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…There is a general perception that the foods included in an LCHF diet are expensive and that most of the people who decide to follow this lifestyle in South Africa are reasonably affluent [22]. This is consistent with the perception that LCHF diets are too expensive for people living in under-resourced communities [23].…”
Section: Introductionsupporting
confidence: 59%
“…Similarly, the lack of support, and conflicting advice from doctors caused confusion and frustration among participants. These experiences with peers and doctors are remarkably similar to that of a much more affluent group of individuals with type 2 diabetes who had also followed an LCHF diet [22]. In both studies, family, peers and/or doctors became more supportive of the participants' efforts after observing their health and weight improvements.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We found that Sham_KD and Sham_SD rats were also KEGG-enriched in these two signalling pathways (AD and PD; Additional le 8: Table S5). Although it is known that a KD promotes high ketone body levels, high fat, low carbohydrates, low calories and other "immediacy" properties [29][30], this study suggests that the ketogenic diet may mediate steroid metabolism reprogramming to treat spinal cord injury rats This study is the rst to reach this conclusion. Steroids include sterols (such as cholesterol, lanosterol, sitosterol, stigmasterol, and ergosterol), bile acids and bile alcohols, steroid hormones (such as adrenal cortex hormones, androgens, and oestrogen), insect ecdysone, cardiac glycosides, saponins, and toad poison [31][32][33].…”
Section: Discussionmentioning
confidence: 76%